2011
DOI: 10.3109/09540261.2011.558833
|View full text |Cite
|
Sign up to set email alerts
|

Mental health impact of the Iraq and Afghanistan conflicts: A review of US research, service provision, and programmatic responses

Abstract: Although documentation that war inflicts psychological casualties dates back to the American Civil War and earlier, most research began after the Vietnam conflict, when studies focused on post-traumatic stress disorder (PTSD). With ongoing conflicts in Iraq and Afghanistan, there has been significant research to illuminate the epidemiology of war-related psychological casualties. Significant findings include an appreciation for the role combat plays in the development of mental disorders, including PTSD and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 75 publications
0
52
0
1
Order By: Relevance
“…3,38 Much of the association between an Afghanistan deployment-related mental disorder and lower rank, Army service and deployment location was likely mediated by combat exposure, which is known to be a strong, consistent and independent predictor of postdeployment mental disorders. 6 However, there was a meaningful incidence of mental disorders related to the Afghanistan mission among personnel who had not had any combat exposure (e.g., those stationed in the United Arab Emirates).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,38 Much of the association between an Afghanistan deployment-related mental disorder and lower rank, Army service and deployment location was likely mediated by combat exposure, which is known to be a strong, consistent and independent predictor of postdeployment mental disorders. 6 However, there was a meaningful incidence of mental disorders related to the Afghanistan mission among personnel who had not had any combat exposure (e.g., those stationed in the United Arab Emirates).…”
Section: Discussionmentioning
confidence: 99%
“…28 The extensive survey data reported by other countries raise the same and other comparability issues. 29 Data from historical conflicts raise even larger issues, 6 including changes in the conceptualization of trauma-related disorders. 30 Studies that have used administrative data on mental health care encounters are more comparable: Hoge and colleagues 2 found that 9%-12% of US Army personnel returning from Iraq had a mental disorder diagnosed within about a year after their return; the proportion related to the most recent deployment was unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of PTSD prevalence rates in U.S. military populations range from 5 to 24.5 percent. Research indicates that rates are higher for service members who deployed to Iraq in support of Operation Iraqi Freedom than for those who deployed to Afghanistan in support of Operation Enduring Freedom, higher among women than among men in the military, and higher for individual service members after deployment relative to before (Fulton et al, 2015;Hoge, Auchterlonie, and Milliken, 2006;Hoge et al, 2004;Maguen et al, 2010;Milliken, Auchterlonie, and Hoge, 2007;Ramchand et al, 2008;Ramchand et al, 2010;Ramchand et al, 2015;Schell and Marshall, 2008;Smith et al, 2007;Wells et al, 2011). Prevalence estimates for depression among service members range from 7.9 to 15 percent, with higher rates reported after deployment, among women relative to men, and among reserve service members relative to those in the active component (Hoge, Auchterlonie, and Milliken, 2006;Hoge et al, 2004;Maguen et al, 2010;Milliken, Auchterlonie, and Hoge, 2007;Ramchand et al, 2008;Ramchand et al, 2015;Schell and Marshall, 2008).…”
Section: Providing Effective Care For Ptsd and Mdd For Service Membersmentioning
confidence: 99%
“…In contrast, recent operations in Iraq and Afghanistan have allowed for PTSD measurement while operations are ongoing and shortly after personnel have returned from deployment. 8 However, the prevalence of PTSD has still been found to differ across different militaries, ranging from 4% to 17% for those in the United States returning from the Iraq War and from 3% to 6% for those returning in the United Kingdom. 9,10 Prevalences in other countries of the world are less well documented.…”
Section: Highlightsmentioning
confidence: 99%